A voxel-based method for designing a numerical biomechanical model patient-specific with an anatomical functional approach adapted to additive manufacturing. Issue 3 (17th February 2019) - Lerebours, Augustin; Marin, Frederic; Bouvier, Salima; Egles, Christophe; Masquelet, Alain-Charles; Rassineux, Alain
Abstract: Here, we describe an original and efficient geometry design approach, based on voxels resulting in a validated model for printability in additive manufacturing. The proposed approach is also designed to be accessible to non-specialists as it does not require specialist skills in computer-assisted-design (CAD). It focuses on biomedical applications, particularly the geometry design of a configurable digital biomechanical model with selected anatomical features based on medical imaging compatible with customization, as might be needed for prosthetic elements. The methodology is based on two main steps. First, an accessible parametrization to medical employees of a configurable biomechanical model is matched specifically to the patient. The configurable model is designed to palliate any kind of potential lack of information from the Digital Imaging and Communication in Medicine (DICOM) file of the medical imaging or partial topological defects but with the least and sufficient number of parameters. For this purpose, the configurable model is segmented in topological areas with a complexity facing solely the desired specification, without regards of potential numerical errors prior AM such as boundary edges, intersecting faces and non-manifold edges. The second step is the voxel-based modelling, easily accessible for medical employees unfamiliar with CAD. Voxels stores the geometric information in a discrete format to facilitate customization by topological operations such as addition and subtraction. The voxelization representation coupled with a smoothing filter, results in a more realistic, robust and closed triangulated model, freed from errors of printability. This method is presented in the context of a trapezium replacement prosthesis prior to selective laser melting (SLM) and diverse post-treatments.